Management of hereditary antithrombin deficiency in pregnancy. Issue 157 (September 2017) - James, Andra H.; Bates, Shannon M.; Bauer, Kenneth A.; Branch, Ware; Mann, Kenneth; Paidas, Michael; Silverman, Neil; Konkle, Barbara A.
Abstract: Antithrombin (AT) deficiency is a high-risk thrombophilia and a rare condition. Despite full anticoagulation during pregnancy and the postpartum period, women with AT deficiency may still be vulnerable to developing venous thromboembolism (VTE), including fatal events. There is limited guidance on the management of AT deficiency in pregnancy, including the role of AT concentrates. Following a comprehensive review of the state of the art with respect to recommendations and guidelines, our expert panel in maternal-fetal medicine, hematology and basic science reached consensus on key issues in the recognition and management of AT deficiency in pregnancy. This paper summarizes the state of the art and summarizes what we believe are best practices with special emphasis on a multidisciplinary approach involving obstetrics and hematology in the care of women with AT deficiency. Highlights: AT deficiency in pregnancy is potentially life-threatening to mother and fetus. The condition necessitates a multidisciplinary approach to management. Confirmation of the diagnosis is critical, as is the stratification of treatment. Management frequently includes anticoagulation and consideration of AT concentrates.